Occam-pi for Programming of Massively Parallel Reconfigurable Architectures. (8th February 2012) - Zain-ul-Abdin,; Svensson, Bertil
Abstract : Massively parallel reconfigurable architectures, which offer massive parallelism coupled with the capability of undergoing run-time reconfiguration, are gaining attention in order to meet the increased computational demands of high-performance embedded systems. We propose that theo c c a m - p i language is used for programming of the category of massively parallel reconfigurable architectures. The salient properties of theo c c a m - p i language are explicit concurrency with built-in mechanisms for interprocessor communication, provision for expressing dynamic parallelism, support for the expression of dynamic reconfigurations, and placement attributes. To evaluate the programming approach, a compiler framework was extended to support the language extensions in theo c c a m - p i language and a backend was developed to target the Ambric array of processors. We present two case-studies; DCT implementation exploiting the reconfigurability feature ofo c c a m - p i and a significantly large autofocus criterion calculation based on the dynamic parallelism capability of theo c c a m - p i language. The results of the implemented case studies suggest that theo c c a m - p i -language-based approach simplifies the development of applications employing run-time reconfigurable devices without compromising the performance benefits.